Telerehabilitation - Kumar, Sajeesh; Cohn, Ellen R. (Health Informatics, 2013)
Telerehabilitation, as a subset of telehealth, is the use of telecommunications to deliver rehabilitation services at a distance and can bridge the gaps created by personnel shortages that exist in underserved and remote areas, as well as serve persons in urban settings who cannot easily leave their homes or offices to seek care. Given the mobile nature of our society, telerehabilitation can enable continuity of care while persons travel for work, vacation and/or education. While the technical capacities to conduct telerehabilitation have surged ahead in the past 10 years, there has been slower, yet ongoing progress in the development of the policies (e.g., legislation; state licensure; reimbursement) that will be required to actualize widespread telepractice service delivery. Telerehabilitation presents a wide-angle view of telerehabilitation worldwide at a seminal time in its development. The book contains contributions from authors across multiple disciplines, as well as a consumer-based perspective.  This book contributes significantly to the current understanding of telerehabilitation, as well as elucidating the immense potential for telerehabilitation-based service delivery to benefit persons with disabilities.